Nucleotide sequence of the Syrian hamster intracisternal A-particle gene: close evolutionary relationship of type A particle gene to types B and D oncovirus genes. - Ono, M (1985)
We determined the complete nucleotide sequence of the intracisternal A-particle gene, IAP-H18, cloned from the normal Syrian hamster liver DNA. IAP-H18 was 7,951 base pairs in length with two identical long terminal repeats of 376 base pairs at both ends. On the coding strand, imperfect open reading frames corresponding to gag and pol of the retrovirus genome were observed, whereas many stop codons were present in the region corresponding to env. The putative H18 gag gene (809 amino acids) had a sequence homologous to the N-terminal half of the mouse mammary tumor virus gag gene and locally to the Rous sarcoma virus gag gene. The putative H18 pol gene (900 residues) was homologous to the Rous sarcoma virus pol gene almost throughout the entire region. Two conserved regions among the retrovirus pol genes have been reported. One presumably corresponds to the DNA polymerase and the RNase H domain, and the other corresponds to the DNA endonuclease domain of the multifunctional protein pol. By the comparison of the deduced amino acid sequences of the putative endonuclease domain of six representative oncovirus genomes, a phylogenetic tree of the oncovirus genomes was constructed, and the intracisternal A-particle (type A) genome was found to be more closely related to the mouse mammary tumor virus (type B) and squirrel monkey retrovirus (type D) genomes.